KOSMOS mesocosm experiment Gran Canaria 2019 on testing the effect of nutrient composition (Si:N) during artificial upwelling: environment, nutrients and carbonate chemistry - Goldenberg, Silvan Urs; Ludwig, Andrea; Tietz, Christiane; Hasani, Megi; Riebesell, Ulf (PANGAEA, 2022)
Physio-chemical data from the mesocosms experiment conducted in the Canary Islands in autumn 2019. Values are depth-integrated averages in (mostly) 2-days intervals over the course of 33 days. The upwelling treatment started on day 6. Oxygen (O2), salinity, temperature, photosynthetically active radiation (PAR) and pH were measured from 0.3 to 2.5 m depth via three replicate CTD casts. Dissolved inorganic carbon (DIC) and the inorganic nutrients nitrite (NO2), combined nitrate and nitrite (NO3 + NO2), ammonia (NH4), phosphate (PO4) and silicate (Si(OH)4) were measured in triplicates on depth integrated water samples from 0 to 2.5 m depth. Total alkalinity (TA) was measured from the same water samples but in duplicates. Then, pCO2 and nitrate was calculated. Methodological details in Goldenberg et al. (doi:10.3389/fmars.2022.1015188).
Keywords: artificial upwelling; carbon dioxide removal; diatoms; GC2019; KOSMOS; negative emission technology; ocean fertilization; silicic acid; Si:N